Real-time high quality HDR illumination and tonemapped rendering - Michael-Grigoriou, Despina; Chrysanthou, Yiorgos (My University, 2010)
Real-time realistic rendering of a computer generated scene is one of the core research areas in computer graphics as it is required in several applications such as computer games, training simulators, medical and architectural packages and many other fields. The key factor of realism in the rendered images is the simulation of light transport based on the given lighting conditions. More natural results are achieved using luminance values near to the physical ones. However, the vast range of real luminances has a far greater range of values than what can be displayed on standard monitors. As a final step to the rendering process, a tonemapping operator needs to be applied in order to transform the values in the rendered image to displayable ones. Illumination of a scene is usually approximated with the rendering equation which solution is a computational expensive process. Moreover, the computational cost increases even more with the increase in the number of light sources and the number of vertices of the objects in the scene. Furthermore, in order to achieve high frame rates, current illumination algorithms compromise the quality with assumptions for several factors or assume static scenes so that they can exploit precomputations. In this thesis we propose a real-time illumination algorithm for dynamic scenes which provides high quality results and has only moderate memory requirements. The proposed algorithm is based on factorization of a new notion that we introduce: fullsphere irradiance, which allows the pre-integration of contribution of all light sources within the same value for any possible receiver. Recent illumination algorithms, including ours, usually use environment maps to represent the incident lighting in the scene. Environment maps enable natural environment lighting conditions to be used by using high dynamic range (HDR) values. Typically the HDR obtained result of the illumination needs to be tonemapped into LDR values that can be displayed on standard monitors. Traditionally tonemapped techniques give emphasis either to frame rate (global operators) or to the quality (local operators) of the resulting image. In this thesis, we propose a new framework: selective tonemapping which addresses both requirements. The key idea of this framework is to apply the expensive computations of tonemapping only to the areas of images which are regarded as important. A full rendering system has been developed which integrates HDR illumination computation and the selective tonemapping framework. Results show high quality images at real¬time frame rates.
Keywords: Computer simulation; Digital computer simulation; Digital images; Computer graphics; High dynamic range imaging